Answer :

__Basic idea:__

√Second order derivative is nothing but derivative of derivative i.e.

√The idea of chain rule of differentiation: If f is any real-valued function which is the composition of two functions u and v, i.e. f = v(u(x)). For the sake of simplicity just assume t = u(x)

Then f = v(t). By chain rule, we can write the derivative of f w.r.t to x as:

√Product rule of differentiation-

√Apart from these remember the derivatives of some important functions like exponential, logarithmic, trigonometric etc..

Let’s solve now:

Given,

y=e^{x} cos x

TO prove :

Clearly from the expression to be proved we can easily observe that we need to just find the second derivative of given function.

Given, y = e^{x} cos x

We have to find

As

So lets first find dy/dx and differentiate it again.

∴

Let u = e^{x} and v = cos x

As, y = u*v

∴ Using product rule of differentiation:

∴

[ ∵ ]

Again differentiating w.r.t x:

Again using the product rule :

[∵

[∵ –sin x = cos (x + π/2)]

Rate this question :

If y = 3 cos(log x) + 4 sin(log x), show that

Mathematics - Board Papers

If x = t^{2}, y = t^{3}, then is

If x = a cos θ + b sin θ, y = a sin θ – b cos θ, show that

Mathematics - Board PapersIf prove that

Mathematics - Exemplar

If y =(tan^{–1}x)^{2}, show that

If y = (tan ^{- 1} x)^{2}, show that (x^{2} + 1)^{2}

Differentiate

**OR**

If x = a(θ – sin θ), y = a(1 + cosθ), find

Mathematics - Board PapersFind if (x^{2} + y^{2})^{2} = xy.

**OR**

If y = 3 cos(log x) + 4 sin(log x), then show that

Mathematics - Board Papers